Initial experience with prostatic urethral lift versus enucleation of the prostate: a retrospective comparative study - Daisuke Obinata; Rio Uehara; Sho Hashimoto; Ken Nakahara; Tsuyoshi Yoshizawa; Junichi Mochida; Kenya Yamaguchi; Satoru Takahashi (BMC Urology, 2023)
Abstract Background This study aimed to assess initial results and patient characteristics of prostatic urethral lift (PUL) compared with those of bipolar transurethral enucleation of the prostate (TUEB) in the treatment of benign prostatic hyperplasia (BPH) in older patients. Methods This retrospective study was conducted at a single institution and involved 25 consecutive patients with BPH who underwent PUL between April 2022 and May 2023. Patient characteristics, operative details, and pre- and postoperative symptom scores were evaluated. The results were compared with those of a previously reported TUEB group (n = 55). Results The mean age of the patients in the PUL group was 74.6 years, and the mean prostate volume was 47.5 ml. The PUL procedure significantly improved urinary symptoms, particularly incomplete emptying (p = 0.041), intermittency (p = 0.005), and weak stream (p = 0.001). The PUL group had higher comorbidity scores (p = 0.048) and included older patients (p = 0.002) than the TUEB group. TUEB showed better improvements in some symptoms and maximum flow rate (p = 0.01) than PUL; however, PUL had a shorter operative time and fewer complications than TUEB (p < 0.001). Conclusion The initial results demonstrate the efficacy and safety of PUL in older patients with BPH. Despite TUEB showing better outcomes in certain aspects than PUL, PUL offers advantages such as shorter operative time and fewer complications. Therefore, PUL can be considered a viable option for high-risk older patients with BPH.